Written Records about Hegumens of Chervleny Yar in the 14th century - A.P. Nikitin (Золотоордынское обозрение)
Objective: To examine written records mentioning the hegumens in the territory of Chervleny Yar during the Golden Horde period. Materials: The study is mainly based on the charters of Metropolitans Theognost and Alexei, concerning the dispute between the Orthodox dioceses of Saray and Ryazan in the 14th century. The results of archaeological research, references to plague outbreaks, and the reconstructed text of Taidula’s charter granted to Metropolitan Theognost provide indirect information for research. Results and novelty of the research: Based on the mention of hegumens in Chervleny Yar in the 14th century in the charters of the Metropolitans Theognost and Alexei, one can assert the existence of several Orthodox monasteries in the territory of this administrative unit of the Golden Horde. The plague, the fiscal policy of Janibek, and the spread of Islam in the Jochid ulus could have been the true reasons for the disappearance of monasteries in the 14th century. The plague epidemic could have completely destroyed the inhabitants of the monastery and the rural district of the cloister. Janibek’s decision to deprive the Orthodox Church of tax benefits could have led to the liquidation of the financial basis for monastic life in the interfluve of the Don and the Khoper after the disappearance of support for monasteries. In addition to all these, the wide proliferation of Islam among the population of Chervleny Yar eliminated the possibility of functioning Orthodox spiritual centers outside of the Russian principalities. The charter of Metropolitan Theognost can be dated between 1334 and 1346–1349. Archaeological search for Christian objects of the Golden Horde period in the interfluve of the Don and the Khoper can be considered as a task for the future.